Technological Interventions in Education: An Empirical Review of Their Impact on Learning Outcomes - Behera, Deepak Kumar (ALSYSTECH Journal of Education Technology, 2023)
This empirical review delves into the ramifications of technological interventions in education on learning outcomes. Drawing on a synthesis of prior empirical research, the review examines the effects of diverse technological interventions, including mobile devices, online learning environments, and educational software, on student achievement, motivation, and engagement. The review underscores the potential benefits of technology-enhanced learning, encompassing improved academic achievement, heightened engagement in learning, and augmented motivation. Additionally, the review emphasizes the significance of tailoring technology-enhanced learning environments to accommodate individual learner attributes and requirements. Furthermore, the review identifies the constraints of technology-enhanced learning and highlights directions for future research, including investigating the efficacy of such interventions for learners from various backgrounds and characteristics. The implications of the findings for policy-making and society are also deliberated.